The effects of fluid ingestion on stress hormones during prolonged exercise in the heat - Paek, S. S.; Jun, T. W. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study was to investigate in the effect of fluid ingestion on stress hormones during prolonged exercise in the heat (Temperature 32 C, relative humidity 61 3%). The results suggested that the level of stress hormones in the blood was increased more when water was not ingested than when water or carbohydrate-electrolyte fluid was ingested. There was no relationship between fluid ingestion and assessing times. These results suggested that fluid ingestion during prolonged exercise in the heat was required for physiological and biochemical stability and homeostasis of human body.